PATHOGENESIS, IMMUNITY, PATHOLOGY AND CLINICAL MANIFESTATIONS OF MEASLES (Scientific Conference on Multidisciplinary Studies, 2025)
Measles (rubeola) is a highly contagious, acute, exanthematous respiratory disease with a characteristic clinical picture and a pathognomonic enanthem: Koplik’s spots, an eruption on the buccal mucous membranes. Measles virus is the only member of the genus Morbillivirus that infects humans. Part of the family Paramyxoviridae, it is related to viruses causing similar infections in other mammals: distemper, rinderpest, morbilli, and peste des petits ruminants. There is only one antigenic type.Virions—pleomorphic spheres with a diameter of 100–250 nm—consist of six proteins.The inner capsid is composed of RNA and three proteins.The outer envelope consists of a matrix protein bearing short surfaceglycoprotein projections or peplomers, one a hemagglutinin (H) and the other a fusion (F) protein.